2016
DOI: 10.1099/mic.0.000382
|View full text |Cite
|
Sign up to set email alerts
|

Microbial nanowires: an electrifying tale

Abstract: Electromicrobiology has gained momentum in the last 10 years with advances in microbial fuel cells and the discovery of microbial nanowires (MNWs). The list of MNW-producing micro-organisms is growing and providing intriguing insights into the presence of such micro-organisms in diverse environments and the potential roles MNWs can perform. This review discusses the MNWs produced by different micro-organisms, including their structure, composition and mechanism of electron transfer through MNWs. Two hypotheses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
39
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 88 publications
(39 citation statements)
references
References 89 publications
0
39
0
Order By: Relevance
“…In this study, a noncontact interaction mode between strains YYL and MLY1 was ensured by separately culturing the two strains while maintaining extracellular metabolite exchange. It is noteworthy that metabolite communication has been widely shown to mediate contact-independent interactions between bacteria (22)(23)(24). Based on these findings, we focused on elucidating the metabolic interaction mechanism between strains YYL and MLY1 by examining the changing profiles of metabolites in the mono-and coculture systems at the optimal pH of 8.3 and a stressful pH of 7.0.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, a noncontact interaction mode between strains YYL and MLY1 was ensured by separately culturing the two strains while maintaining extracellular metabolite exchange. It is noteworthy that metabolite communication has been widely shown to mediate contact-independent interactions between bacteria (22)(23)(24). Based on these findings, we focused on elucidating the metabolic interaction mechanism between strains YYL and MLY1 by examining the changing profiles of metabolites in the mono-and coculture systems at the optimal pH of 8.3 and a stressful pH of 7.0.…”
Section: Discussionmentioning
confidence: 99%
“…2), varied intercellular connective systems exist in Bacillus subtilis, Geobactor spp., and other bacterial species [39] (reviewed in ref. [40]). These connections occur both intra-and inter-specifically with nanowires or nanotubes bridging the cells [39], or with outer membrane extensions and vesicle chains as observed in Shewanella oneidensis [41].…”
Section: Induction Formation and Cohesiveness Of Coloniesmentioning
confidence: 99%
“…Several mechanisms for EET have been described in both Gram-positive and Gram-negative bacteria 22, 23 . In some bacteria, microbial nanowires, composed of extracellular filamentous protein fibers and/or of cytochrome-associated fibers, have been proposed to aid EET by directly connecting the bacterial cell surface to extracellular metal oxides, or alternatively, by interacting with extracellular soluble redox mediators 23, 24 . Biochemical and structural analysis have recently demonstrated that the conductive filaments of Geobacter sulfurreducens consist of polymerized chains of the hexaheme cytochrome OmcS 25 .…”
Section: Introductionmentioning
confidence: 99%